2013
DOI: 10.1016/j.jcp.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary variables for 3D multiscale simulations in heterogeneous porous media

Abstract: The multiscale control-volume methods for solving problems involving flow in porous media have gained much interest during the last decade. Recasting these methods in an algebraic framework allows one to consider them as preconditioners for iterative solvers. Despite intense research on the 2D formulation, few results have been shown for 3D, where indeed the performance of multiscale methods deteriorates. The interpretation of multiscale methods as vertex based domain decomposition methods, which are non-scala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The multiscale method itself can be generalized to N-spatial dimensions [83]. Note however that the quality of the coarse discretization may degenerate as the number of dimensions increase [96]. In three dimensions the fractures, now as planes, still form natural boundary conditions for the local problems and represent the global connections in the domain.…”
Section: Further Directionsmentioning
confidence: 99%
“…The multiscale method itself can be generalized to N-spatial dimensions [83]. Note however that the quality of the coarse discretization may degenerate as the number of dimensions increase [96]. In three dimensions the fractures, now as planes, still form natural boundary conditions for the local problems and represent the global connections in the domain.…”
Section: Further Directionsmentioning
confidence: 99%
“…The model contains two formations: The Tarbert formation at the top of the model represents a prograding near-shore formation, which even though it exhibits orders of magnitude variations in the permeabilities, is relatively smooth and tends to be well resolved by most multiscale methods. The Upper Ness formation in the lower part of the model is fluvial and has proved to be more challenging, in particular for finite-volume type multiscale methods that rely on some form of pressure extrapolation for localization, see e.g., [38,48,56] and references therein.…”
Section: Spe10: Horizontal Layersmentioning
confidence: 99%
“…Whereas the solution quality is generally very good for both solvers for Tarbert, MsRSB clearly outperforms MsFV on Upper Ness. Several authors have independently shown that the MsFV method has issues with coarse scale stability in the presence of channelized, high-contrast formations and will suffer from strong unphysical oscillations that may prevent iterative versions of the method from converging properly, see e.g., (Sandvin et al 2013;Wang et al 2014;Møyner and Lie 2014a) and references therein. MsRSB is much more robust and does not suffer from such problems and therefore gives solutions of similar accuracy for the smooth and channelized layers.…”
Section: Accuracy For Single-phase Flowmentioning
confidence: 99%